Common variants in maturity-onset diabetes of the young genes and future risk of type 2 diabetes. - Holmkvist, J; Almgren, P; Lyssenko, V; Lindgren, C; Eriksson, K; Isomaa, B; Tuomi, T; Nilsson, P; Groop, L (2008)
OBJECTIVE: Mutations in the hepatocyte nuclear factor (HNF)-1alpha, HNF-4alpha, glucokinase (GCK), and HNF-1beta genes cause maturity-onset diabetes of the young (MODY), but it is not known whether common variants in these genes predict future type 2 diabetes. RESEARCH DESIGN AND METHODS: We tested 14 previously associated polymorphisms in HNF-1alpha, HNF-4alpha, GCK, and HNF-1beta for association with type 2 diabetes-related traits and future risk of type 2 diabetes in 2,293 individuals from the Botnia study (Finland) and in 15,538 individuals from the Malmö Preventive Project (Sweden) with a total follow-up >360,000 years. RESULTS: The polymorphism rs1169288 in HNF-1alpha strongly predicted future type 2 diabetes (hazard ratio [HR] 1.2, P = 0.0002). Also, SNPs rs4810424 and rs3212198 in HNF-4alpha nominally predicted future type 2 diabetes (HR 1.3 [95% CI 1.0-1.6], P = 0.03; and 1.1 [1.0-1.2], P = 0.04). The rs2144908 polymorphism in HNF-4alpha was associated with elevated rate of hepatic glucose production during a hyperinsulinemic-euglycemic clamp (P = 0.03) but not with deterioration of insulin secretion over time. The SNP rs1799884 in the GCK promoter was associated with elevated fasting plasma glucose (fPG) concentrations that remained unchanged during the follow-up period (P = 0.4; SE 0.004 [-0.003-0.007]) but did not predict future type 2 diabetes (HR 0.9 [0.8-1.0], P = 0.1). Polymorphisms in HNF-1beta (transcription factor 2 [TCF2]) did not significantly influence insulin or glucose values nor did they predict future type 2 diabetes. CONCLUSIONS: In conclusion, genetic variation in both HNF-1alpha and HNF-4alpha predict future type 2 diabetes, whereas variation in the GCK promoter results in a sustained but subtle elevation of fPG that is not sufficient to increase risk for future type 2 diabetes.